Implementation of Al-Ghazali Maslahah Concept In Islamic Economic Activities - Muhammad Maksum (SALAM: Jurnal Sosial dan Budaya Syar-i, 2022)
The article covers Al-Ghazali's view on the use of maslahah mursalah as the basis for establishing law in the field of sharia economics. The concept of maslahah mursalah is debated among ulama to be used as the basis for establishing law. The maslahah provides opportunities for the adoption of new innovations that were not previously discussed among ulama and were not rejected by religion. On the other hand, the economy needs sharia support to continue to run in accordance to religious guidance and adapt to the times. By comparing economic principles and maslahah theory, al-Ghazali's view that accepts the implementation of maslahah is found as a solutional view. Nevertheless, al-Ghazali provided conditions and restrictions on the use of maslahah in the economic field so that they will not be chaotic and uncontrolled.Keywords: maslahah mursalah; al-Ghazali; Islamic economics; religious purpose Abstrak: Artikel ini mengulas pandangan Al-Ghazali tentang penggunaan maslahat mursalah sebagai dasar penetapan hukum di bidang ekonomi syariah. Konsep maslahat mursalah diperdebatkan di kalangan ulama untuk dijadikan dasar penetapan hukum. Maslahat ini memberi peluang adopsi inovasi-inovasi baru yang sebelumnya tidak dibahas di kalangan ulama dan tidak ditolak pula oleh agama. Di sisi lain, ekonomi membutuhkan dukungan syariah agar tetap berjalan sesuai tuntunan agama dan beradaptasi dengan perkembangan zaman. Dengan membandingkan prinsip ekonomi dan teori maslahat, ditemukan pandangan al-Ghazali yang menerima penerapan maslahat tersebut sebagai pandangan solutif. Meskipun begitu, al-Ghazali memberikan persyaratan dan pembatasan penggunaan maslahat tersebut dalam bidang ekonomi agar tidak liar dan tidak terkendali.Kata kunci: Maslahah Mursalah; Al-Ghazali; Ekonomi Islam; Tujuan Keagamaan